Accounting Principles (Policies) with Regard to the Property, Plant and Equipment of Companies from the Hotel and Restaurant Sector Listed on the Warsaw Stock Exchange - Różańska , Ewa (Studia Oeconomica Posnaniensia, 2014)
This article presents an analysis of the accounting policies of companies with regard to property, plant and equipment. The first part of the work presents the development of enterprise accounting policies. The second part contains an analysis of the instruments of accounting policies with regard to property, plant and equipment conducted according to the requirements of IAS 16 and Polish accounting law. The final part contains an empirical study relating to the disclosure of property, plant and equipment in financial statements, involving a population of Polish companies from the hotel and restaurant sector listed on the Warsaw Stock Exchange as at 31 December 2013.